2009
DOI: 10.1143/jjap.48.085502
|View full text |Cite
|
Sign up to set email alerts
|

Metal Oxide Film for Growing Vertically Aligned Single-Walled Carbon Nanotubes

Abstract: A conventional TEM was extended to a time-resolving instrument by installing a pulsed microchannel plate as a lowcost time-resolving image detector and a pulsed electron beam shutter. The technique provides electron micrographs and diffraction pictures of non-recurring events on the nanosecond/micrometre scale within a commercial TEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…This is likely because the cluster effect may become dominant so that larger particles are easily formed as the film thickness increases. 15 In Fig. 1͑e͒, it is shown that the mean diameter of the size distribution is approximately 8 nm while the initial thickness is 4.5 nm.…”
mentioning
confidence: 89%
“…This is likely because the cluster effect may become dominant so that larger particles are easily formed as the film thickness increases. 15 In Fig. 1͑e͒, it is shown that the mean diameter of the size distribution is approximately 8 nm while the initial thickness is 4.5 nm.…”
mentioning
confidence: 89%